MENINGKATKAN KEMAMPUAN KOGNITIF ANAK USIA 4-5 TAHUN MELALUI PERMAINAN BUKA TUTUP GEOMETRI WARNA (KATUP GEWAR) DI TK ISLAMIC CENTER SAMARINDA - Melda Fitriani K; Arbayah; Sjamsir, Hasbi (BEduManagers Journal : Borneo Educational Management and Research Journal, 2022)
The study "Improving the Cognitive Ability of Children Aged 4-5 Years Through the Game "Open and Close Color Geometry" (Gewar Valve) at TK Islamic Center Samarinda" is a professional ability strengtheningresearch that aims to improve children's cognitive abilities, especially regarding the introduction of geomteri shapes and colors to children. This research was conducted for two cycles starting from October 10 - 22, 2021 at the kindergarten. Islamic Center Samarinda. The subject of the study was the children of group A class KH. Djafar Sabran who will play gewar valve. This study used observation and documentation techniques for observation and data collection needed. While the instruments used are observation sheets and rubrics for assessing children's cognitive skills. The success of this study was achieved if 70% of all children were able to complete the game with the achievement of the Develop According to Expectations (BSH) level. In the first cycle, children's achievement only touched 45% so this study was continued in cycle two. Improvements in cycle onefocused on adding media so that it could be used by all children, in addition to improvements made to time and class management. The implementation of cycle II resulted in the achievement of children who succeeded in achieving the level of Developing According to Expectations (BSH) of 70%. So that this research can be said to be successful and the ketup gewar game deserves to be used as a learning medium for the next game.